Autoscopic Phenomena - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1989)
Ten patients with seizures and autoscopic phenomena, such as seeing one's double, are reported and 33 additional cases in the literature are reviewed from the Medical Neurology Branch, Division of Intramural Research, National Institute of Neurological Disorders and Stroke, Bethesda, MD; and the Department of Neurology, New York Hospital, New York, NY.